Serum antibody response to proteins of Moraxella (Branhamella) catarrhalis in patients with lower respiratory tract infection. - Christensen, J J (1995)
We searched for antibodies against Moraxella (Branhamella) catarrhalis proteins in the sera of patients with lower respiratory tract infection. Sera from 48 patients with M. catarrhalis and 39 patients without M. catarrhalis in their lower respiratory tract specimens were studied by a gel electrophoresis-immunoperoxidase technique; sera from 23 healthy adult blood donors were also included. Immunoglobulin G (IgG) antibodies against a 28-kDa protein were found significantly more frequently in patients with M. catarrhalis in lower respiratory tract specimens (71%) than in patients without M. catarrhalis in lower respiratory tract specimens (28%) or healthy adult blood donors (22%). Seroconversion, from the acute to the convalescent stages, occurred in at least eight patients with M. catarrhalis and in one patient without detectable M. catarrhalis. IgG antibodies against other M. catarrhalis proteins were found in most sera, including those obtained from blood donors. By adsorption experiments the 28-kDa protein was demonstrated to be surface exposed. IgM antibodies against an 85-kDa protein were found in serum from one patient from whom M. catarrhalis and Streptococcus pneumoniae were isolated from the lower respiratory tract, while IgA antibodies against M. catarrhalis proteins could not be detected in any serum specimen.